Pengaruh Citra Merek dan Kualitas Produk terhadap Minat Beli Baju Thrifthing Dimediasi Kepercayaan dan Sikap Konsumen dalam Perspektif Bisnis Islam - Nabila Khasanah Ummah; Okta Supriyaningsih; Erlin Kurniati (Jurnal bintang manajemen, 2025)
The development of trade has provided very free space for movement in every transaction so that goods and services are easily owned and consumed by consumers, one of which is thrifting clothing which is one of the most basic needs for humans which is very important to use to cover and protect the body in every his activities. The aim of this research is to analyze the influence of brand image on consumer trust, the influence of product quality on consumer trust, the mediating role of consumer trust on the relationship between brand image and product quality, the mediating role of consumer attitudes on the relationship between brand image and product quality, the influence of brand image on buying interest, and the influence of product quality on purchasing interest. The influence of brand image and product quality on interest in buying thrift clothes in the growing fashion industry. This research also examines the mediating role of consumer beliefs and attitudes in the Islamic business perspective. By using regression and mediation analysis methods, the results of this research can provide valuable insight for business people, especially in understanding the preferences and behavior of Muslim consumers who are increasingly consuming fashion products. The research results conclude that the relationship between brand image has a positive and significant effect on consumer trust. , The relationship between product quality has a positive and significant effect on consumer trust, The mediating role of consumer trust strengthens the relationship between brand image and product quality, The mediating role of consumer attitude strengthens the relationship between brand image and product quality, The relationship between brand image has a positive and significant effect on purchase intention, and The relationship between product quality has a positive and significant effect on purchasing interest.